Oral antioxidants improve leg blood flow during exercise in patients with chronic obstructive pulmonary disease - Rossman, Matthew J.; Trinity, Joel D.; Garten, Ryan S.; Ives, Stephen J.; Conklin, Jamie D.; Barrett-O'Keefe, Zachary; Witman, Melissa A. H.; Bledsoe, Amber D.; Morgan, David E.; Runnels, Sean; Reese, Van R.; Zhao, Jia; et al. (American journal of physiology. Heart and circulatory physiology, 2015)
The consequence of elevated oxidative stress on exercising skeletal muscle blood flow as well as the transport and utilization of O 2 in patients with chronic obstructive pulmonary disease (COPD) is not well understood. The present study examined the impact of an oral antioxidant cocktail (AOC) on leg blood flow (LBF) and O 2 consumption during dynamic exercise in 16 patients with COPD and 16 healthy subjects. Subjects performed submaximal (3, 6, and 9 W) single-leg knee extensor exercise while LBF (Doppler ultrasound), mean arterial blood pressure, leg vascular conductance, arterial O 2 saturation, leg arterial-venous O 2 difference, and leg O 2 consumption (direct Fick) were evaluated under control conditions and after AOC administration. AOC administration increased LBF (3 W: 1,604 ± 100 vs. 1,798 ± 128 ml/min, 6 W: 1,832 ± 109 vs. 1,992 ± 120 ml/min, and 9W: 2,035 ± 114 vs. 2,187 ± 136 ml/min, P < 0.05, control vs. AOC, respectively), leg vascular conductance, and leg O 2 consumption (3 W: 173 ± 12 vs. 210 ± 15 ml O 2 /min, 6 W: 217 ± 14 vs. 237 ± 15 ml O 2 /min, and 9 W: 244 ± 16 vs 260 ± 18 ml O 2 /min, P < 0.05, control vs. AOC, respectively) during exercise in COPD, whereas no effect was observed in healthy subjects. In addition, the AOC afforded a small, but significant, improvement in arterial O 2 saturation only in patients with COPD. Thus, these data demonstrate a novel beneficial role of AOC administration on exercising LBF, O 2 consumption, and arterial O 2 saturation in patients with COPD, implicating oxidative stress as a potential therapeutic target for impaired exercise capacity in this population.